Antithrombin concentrate use in sepsis‐associated disseminated intravascular coagulation: re‐evaluation of a 'pendulum effect' drug using a nationwide database. (29th January 2018) - Tagami, T.
Abstract : Summary: There are four systematic reviews and meta‐analyses of trials of antithrombin use for sepsis or critically ill patients published to date with conflicting results. The two studies that showed positive results used data only from septic patients who were also diagnosed with disseminated intravascular coagulation (DIC), whereas the two studies showing negative results included data from all septic and/or critically ill patients in their analyses. We believe that the underlying diseases of the study population must be as homogeneous as possible when evaluating treatment efficacy for sepsis‐associated DIC. We published two large‐scale antithrombin studies of sepsis‐associated DIC using a Japanese nationwide database. The above‐mentioned DIC studies reported significant associations between antithrombin use and better 28‐day mortality in both populations (DIC‐associated with severe pneumonia, n = 9075; and with severe abdominal sepsis, n = 2164). Now is the time to initiate multinational antithrombin trials exclusively among sepsis‐associated DIC patients.